Ecossistema de inovação social, desenvolvimento comunitário e microcrédito: proposição de um framework - Castelo, Joelma Leite (2023)
In this thesis, we seek to understand the dynamics of the process and the result of a social innovation initiatives through the empirical experience of community development and microcredit programs. To this end, three articles were developed with the purpose of filling gaps identified in the literature that investigates the process and the result of local social innovation initiatives. In the first article, investigates the characteristics of social innovation in a local community beneficiary of a community development program from a process perspective. For that, field research was carried out in the light of the theoretical model of Tardif and Harrison (2005), with a qualitative approach, in which semi-structured interviews, direct observation with a field diary, and documental analysis were carried out. The results allowed identifying and exploring the five categories of analysis present in the theoretical model used: (i) transformations; (ii) innovative nature; (iii) innovation; (iv) actors; and (v) processes. The analyzes corroborate the character of social innovation associated with the development of the territory. On the other hand, processes need greater professionalization and formalization, which could reduce financial dependence on public bodies. As empirical-theoretical implications for the SI and public policies aimed at territory development field agenda, the work advances in understanding the SI dynamics in local communities and social organizations, highlighting the role of social projects in combating vulnerabilities and social inequalities, which made it possible to outline the profile of the actors involved and to systematize models and processes applied in the context of the investigated community, serving as a panorama for other similar contexts. The second article evaluates the dimensions of social innovations and the roles of social actors in microcredit from the perspective of results, based on the social innovation classification scale elaborated by D'Amario and Comini (2020). With this, an experience survey with a mix approach (qualitative and quantitative) was carried out with beneficiaries of the Crediamigo/BNB microcredit program, in Fortaleza/CE. The results showed that social innovation actions promote socioeconomic inclusion, allowing income generation, empowerment, and improvement in quality of life. Additionally, a cluster analysis was developed, which allowed characterizing different profiles of beneficiaries, contributing to the expansion of understanding of the dimensions of social innovation and the roles of social actors in the investigated context. In the third article, an analytical framework for community social innovation is proposed from the perspective of the ecosystem approach based on the empirical experience between community development and microcredit projects. This investigation has a qualitative nature, with exploratory-descriptive purposes. This is a case study, through field research and qualitative evaluation with 38 beneficiaries of the Crediamigo/BNB microcredit program, from the Bom Jardim unit, in Fortaleza/CE. The study allowed systematizing a framework integrating the process and result of SI initiatives applied in the investigated context, serving as a mechanism for the promotion of Community Social Innovation Ecosystems [EISC], as well as a methodological instrument for future regional economic and social public policies. As theoretical-empirical contributions, the study advances in understanding SI dynamics in local communities and social organizations, highlighting the role of intersectoral partnerships (public, private, and third sector) in combating vulnerabilities and social inequalities. In addition, the study contributes to understanding the dynamics of community management and governance, bringing reflections on the role played by QH actors (government, companies, civil society, and academia) in the process of planning, articulating, coordinating, and implementing innovative practices and entrepreneurs in the social, cultural, educational, environmental, and economic fields. Thus, it is argued in this thesis that social 10 innovation initiatives in the microfinance environment and vulnerable communities occur from the articulation between their beneficiaries and various social actors through intersectoral collaborations (public, private and the third sector), in which different publics engage in the solution of social problems that can be explained in a ecosystem approach and analyzed through a Community Social Innovation Ecosystem [EISC] framework, thus constituting a possible innovative public policy co-created with citizens for solutions of social problems.